Dictionary of water and waste management - Smith, Paul G., (Butterworth-Heinemann, ;IWA Publishing, 2005)
"The Dictionary of Waste and Water Treatment was published in 1981 and was aimed at treatment and treatment design. Over the last 20 years, areas such as air pollution control, solid waste management, hazardous waste management, pipeline management (leakage control, pipeline and sewer renewal) and environmental management systems have all become increasingly important. To reflect this shift, the title has been amended to include the word 'management'." "The dictionary has been completely revised and updated to encompass all the changes of the last 20 years to become the most comprehensive dictionary of water and waste management available." -- Jacket.